An Unusual Cause of Chronic Headache in an Adolescent Boy: A Case Report - Yoganathan, Sangeetha; Mariappan, Ramamani; Sudhakar, Sniya Valsa; Mani, Sunithi Elizabeth; Mathew, Vivek; Thomas, Maya; Aboobacker, Fouzia Nambiathayil (Neuropediatrics, 2019)
Spontaneous intracranial hypotension (SIH) is an under-diagnosed cause of headache in children and adolescents. SIH results from cerebrospinal fluid (CSF) leak due to breach in the dura mater and the etiology for dural breach is often diverse. We report an adolescent boy who presented with chronic episodic headache that later progressed to daily headache. There was a typical history of worsening of headache on upright position and relief of headache on lying down. He was treated with migraine prophylaxis in another hospital but there was no response. Marfanoid features and brisk deep tendon reflexes were observed on clinical examination. Brain magnetic resonance imaging (MRI) revealed sagging of the brain stem, pachymeningeal enhancement, and tonsillar herniation. MRI of spine myelogram confirmed multiple levels of CSF leak. He was initially managed with supportive measures and fluoroscopic-guided fibrin glue injection. Although child remained symptom-free for the next 6 months, he again developed headache. MRI and computed tomography spine myelogram revealed a meningeal diverticulum in the lumbar spine. He was managed with an autologous epidural blood patch and he has been well since then. In this report, we highlight the clinical and radiological pointers to the presence of SIH in children with recurrent headache.
Keywords: headache; spontaneous intracranial hypotension; CSF leak; epidural blood patch; fibrin glue injection